2019
DOI: 10.1016/j.celrep.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CRISPR AcrIIA5 Potently Inhibits All Cas9 Homologs Used for Genome Editing

Abstract: SUMMARY CRISPR-Cas9 systems provide powerful tools for genome editing. However, optimal employment of this technology will require control of Cas9 activity so that the timing, tissue specificity, and accuracy of editing may be precisely modulated. Anti-CRISPR proteins, which are small, naturally occurring inhibitors of CRISPR-Cas systems, are well suited for this purpose. A number of anti-CRISPR proteins have been shown to potently inhibit subgroups of CRISPR-Cas9 systems, but their maximal inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…S7). Conversely, AcrIIA5 displayed strong inhibitory activity toward both SauCas9 and SpyCas9, as recently shown (30), while AcrIIA6 did not show any inhibition of either of the two Cas9s.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…S7). Conversely, AcrIIA5 displayed strong inhibitory activity toward both SauCas9 and SpyCas9, as recently shown (30), while AcrIIA6 did not show any inhibition of either of the two Cas9s.…”
Section: Resultssupporting
confidence: 76%
“…We next tested three known Acrs for their ability to inhibit SauCas9-mediated genome editing in mammalian cells, including the robust SpyCas9 inhibitor AcrIIA4 (10), the broad-spectrum type II-A Cas9 inhibitor AcrIIA5 (12,30), and the speciesspecific Streptococcus thermophilus Cas9 inhibitor AcrIIA6 (12). While AcrIIA4 prevented genome editing by SpyCas9 as expected (10), we found that it had no effect against SauCas9 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…To date, inhibition of target binding is the prevalent strategy. Thirteen anti-CRISPR proteins interfere with target recognition and binding (type I-F AcrIF1, AcrIF2 and AcrIF10 [34][35][36][37]; type II-A AcrIIA2, AcrIIA4, AcrIIA5 and AcrIIA6 [38][39][40][41][42][43][44][45][46][47]; type II-C AcrIIC3, AcrIIC4 and AcrIIC5 [48][49][50][51]; type V-A AcrVA1, AcrV4A and AcrVA5 [52][53][54][55][56][57][58]), while only five-block target cleavage (type I-E AcrIE1 [29,59]; type III-B AcrIIIB1 [12]; type I-F AcrIF3 [26,27]; type II-C AcrIIC1 and AcrIIC3 [48][49][50]) ( Figure 1). Given that DNA binding is the ratelimiting step of Cascade and Cas9-mediated interference activities [60,61], altering this step is, therefore, an efficient way to inactivate CRISPR-Cas interference.…”
Section: Inhibition Of Crispr-cas Interferencementioning
confidence: 99%
“…Noteworthy, AcrVA1 mimics the PAM to position its catalytic residues close to the crRNA substrate [57]. Interestingly, the type II-A AcrIIA5 anti-CRISPR protein was recently shown to lead to sgRNA cleavage at multiples sites out of the crRNA spacer sequence [45]. However, whether or not this anti-CRISPR protein also has a nuclease activity remains to be determined.…”
Section: Enzymatic Modification Of Crispr-cas Componentsmentioning
confidence: 99%